Factors influencing the intention to adopt internet banking / Mohd Fikri Jamari - Jamari, Mohd Fikri (Faculty of Business and Management, 2015)
The purpose of this study is to determine the factors that influence the intention to adopt internet banking in Johor Bahru area. This study involve a total of 120 questionnaires that been distributed to random respondent in selected location (Johor Bahru) using a convenience sampling method. The data collected being analyzed through several analyses such as frequency analysis, normality analysis, reliability analysis, descriptive analysis, correlation analysis, and multiple regression analysis using Statistical package for the social science (SPSS) version 21.0. In addition, this study found that all independent variables have a significant relationship on intention to adopt internet banking. Other than that, this study is very important for the service provider who plan to promote new forms of banking or to innovate their services.